Duties and Responsibilities of the Principal in Madrasa towards Teachers’ Professionalism Development - Totok Sudarmanto; Abd. Muis; Mundir Mundir; Zainal Abidin (The Faculty of Education and Teaching Training, 2022)
The purpose of this study was to describe the role of the principal as a leader and manager in developing teacher professionalism. This research uses a case study approach. Data was obtained by observation, interviews, and document review. Data analysis used interactive analysis consisting of data reduction, data presentation, and conclusions. This research resulted in three findings. First, as the innovator, duties and responsibilities of madrasah principals are enriching insight and related information about madrasa, opening a new madrasa program, restructuring madrasah, conducting reinforcement, developing the professionalism of teachers individually and in teams, managing the physical environment, and performing alternation. Second, as the motivator, duties and responsibilities of madrasa principals are provide a spiritual approach, apply the motto of ki hadjar dewantara motto